Diabetes Mellitus and Renal Function: Current Medical Research and Opinion - Shahwan, Moyad; Hassan, Nageeb; Shaheen, Rima A.; Gaili, Ahmed; Jairoun, Ammar Abdulrahman; Shahwan, Monzer; Najjar, Osama; Jamshed, Shazia (Current Diabetes Reviews, 2021)
Diabetes mellitus (DM), which is defined as high blood glucose level, is a major public health issue worldwide. An enormous amount of data has been gathered regarding DM as populations have been living with it for more than a decade; however, continually updating our knowledge of DM remains important. Comorbidities are among the major challenges associated with DM. Poorly controlled DM, especially type 2 DM (T2DM), is considered a risk factor for many diseases, including but not limited to chronic kidney disease (CKD). Complications might appear over time as the aging process changes body functions; moreover, a significant number of antidiabetic medications are eventually cleared by the kidneys, thereby increasing the burden on kidney function and placing diabetic patients at risk. The significantly high number of patients with uncontrolled diabetes resulting from kidney disease shows the impact of this condition on the quality of life of patients. This review presents an overview of the pathophysiology, etiology, and prevalence of CKD and abnormal renal parameters correlated with poorly controlled T2DM, with an emphasis on clinical studies involving the association between vitamin D insufficiency/deficiency and CKD among patients with T2DM.
Keywords: chronic kidney disease